World of Copper in the 19th Century: An Introduction - Saunders, Olivia; Evans, Chris (Revista de Historia Social y de las Mentalidades, 2017)
This article describes the “world of copper”, that is to say the time span when the world copper trade was under the hegemony of the swansea founders. It does, therefore, in the first place it establishes the times of boom and decadence of the “world of copper”. Secondly, it describes and analyses the structure of the welsh copper enterprises and finally it accounts for the sailing routes and migratory processes that made it possible.
Keywords: World of Copper; Copper Mining; Swansea; Migrations